(untitled) (Revista Contexto & Educação, 2025)
The Revista Educação & Contexto presents a dossier titled "Teacher Training and Practice for/in Inclusive Education – Challenges and Perspectives for Transformative Teaching," organized by Professor Dr. Cleusa Inês Ziesmann, a faculty member at the Federal University of the Southern Frontier – Cerro Largo/RS campus. This dossier is part of the "V International Seminar on Inclusion in Higher Education," which took place from November 6 to 8, 2024, at the Faculty of Forestry Sciences, National University of Misiones, in Eldorado – Misiones, Argentina.